Shotgun proteomic analysis of the secretome of bovine endometrial mesenchymal progenitor/stem cells challenged or not with bacterial lipopolysaccharide - de Moraes, Carolina Nogueira [UNESP]; Maia, Leandro [UNESP]; de Oliveira, Eliandre; de Paula Freitas Dell'Aqua, Camila [UNESP]; Chapwanya, Aspinas; da Cruz Landim-Alvarenga, Fernanda [UNESP]; Oba, Eunice [UNESP] (Elsevier, 2017)
The use of the conditioned medium (CM) for diseases treatment is based on its enrichment with biomolecules with therapeutic properties and themselves have a beneficial effect. Secretome of bovine endometrial mesenchymal progenitor/stem cells (eMSCs) using a proteomics approach is until now unknown. This work aimed to evaluate the secretome of bovine eMSCs-CM challenged or not with lipopolysaccharide (LPS). For this, eMSCs characterized were challenged (TG) or not (CG). The CM was collected 12 h after stimulation and submitted to mass spectrometry analysis. The classification of identified proteins was done by PANTHER according to biological processes, molecular function, cellular component and protein class. 397 protein groups were identified in TG and 302 in CG. We observed positive enrichment for antibacterial response proteins, macrophage activation function, receptor-mediated endocytosis, hydrolase activity, inhibitory enzyme in TG, and for activity structural molecule and intermediate filament cytoskeleton in the CG. Our experimental model shows that eMSCs respond to LPS in the concentration used and can be used to study immune-inflammatory response, besides of the secretion of proteins mainly related to tissue remodeling, immune response and angiogenesis which is an interesting feature for use in cell therapy.
Keywords: Cow; Endometrial mesenchymal cells; nanoLC–MS/MS; Protein; Uterus